A Retrospective Comparative Analysis of Minimally Invasive Osteosynthesis and External Fixation in the Treatment of Long Bone Fractures in Cats - qizi, Aytmuratova Mehribanu Orazbay; Ilalatdinovna, Kamalova Aynura (American Journal of Botany and Bioengineering, 2025)
This retrospective study compares the efficacy, complication rates, and functional recovery of Minimally Invasive Osteosynthesis (MIO) and External Fixation (EF) techniques in the treatment of long bone fractures in cats. A total of 16 cats were analyzed (8 treated with MIO, 8 with EF). Time to bone union, complication frequency, and time to weight-bearing were evaluated. The average time to bone healing was 6.3 weeks (SD ± 1.1) in the MIO group and 8.0 weeks (SD ± 1.4) in the EF group (p = 0.02). Complications occurred in 12.5% of the MIO group and 37.5% of the EF group (p = 0.03). Weight-bearing resumed earlier in the MIO group (mean: 3.0 weeks) compared to the EF group (mean: 4.6 weeks; p = 0.01). MIO is preferable for simple fractures, while EF remains important for complex fractures. These findings may assist veterinary surgeons in making evidence-based treatment decisions.